Molecular identification of Trypanosoma theileri (Laveran, 1902) in cattle from two slaughterhouses in Ecuador and its relation with other haemotropic agents - Chávez-Larrea, María Augusta; Cholota-Iza, Cristina; Cueva-Villavicencio, Jorge; Yugcha-Díaz, Michelle; Ron-Román, Jorge Washington; Rodríguez-Cabezas, Andrea; Saegerman, Claude; Reyna-Bello, Armando (Frontiers in Veterinary Science, 2023)
Trypanosoma theileri is a worldwide distributed haemoparasite that has been reported throughout the American continent in various species, including bovines, buffaloes and bats. In bovines, high incidence of T. theileri can be harmful when associated with other infections or under stress situations. There is little information on this hemoflagellate in Ecuador, which prompted the study and molecular identification of the trypanosomes collected in two slaughtering centers. Between February and April 2021, a total of 218 samples of bovine blood were collected in abattoirs located in the Andean region of Quito (n= 83) and in the coastal region, in Santo Domingo (n=135). Quito public Slaughterhouse is the biggest in Ecuador, and for that, they receive animals from all country; on the other hand, Santo Domingo's Slaughterhouse is a small one where mainly females from the region are sacrificed and some males. The samples were evaluated using two molecular tests, the PCR cathepsin L-like (CatL) specific for T. theileri and for the positive samples, a Nested PCR that targets the ITS of the 18S gene. The corresponding PCR products were sequenced, analyzed by BLAST/ NCBI and the sequences were used to build a concatenated phylogenetic tree, using the MEGA XI software. Overall, 34 out of the 218 samples, (15.6%) were positive to T. theileri by PCR CatL, resulting from 20/83 (24.1%) positives from the Quito abattoir and 14/135 (10.4%) from the Santo Domingo slaughterhouse. These prevalence rates were found to be significantly different (p= 0.006). According to the phylogenetic tree based on the CatL and ITS concatenated sequences (n=13), the two novel Equatorial T. theileri isolates, ThI (n=7) and ThII (n=6) are closely related and associated to the IC, IB and IIB genotypes, present in Brazil, Venezuela and Colombia. Thirty-one out of the thirty-four T. theileri-positive bovines were co-infected with other haemotropic pathogens, Anaplasma marginale Babesia spp and T. vivax. This study presents the molecular identification and genotypification of T. theileri isolated from cattle in Ecuador through the analysis of CAtL and ITS sequences, and the high frequency of coinfection of this hemoflagellate with other blood haemotropic organisms.